Novel Strategy for the Synthesis of Ultra‐Stable Single‐Site Mo‐ZSM‐5 Zeolite Nanocrystals. (18th August 2020) - Konnov, Stanislav V.; Dubray, Florent; Clatworthy, Edwin B.; Kouvatas, Cassandre; Gilson, Jean‐Pierre; Dath, Jean‐Pierre; Minoux, Delphine; Aquino, Cindy; Valtchev, Valentin; Moldovan, Simona; Koneti, Siddardha; Nesterenko, Nikolai; et al.
Abstract: The current energy transition presents many technological challenges, such as the development of highly stable catalysts. Herein, we report a novel "top‐down" synthesis approach for preparation of a single‐site Mo‐containing nanosized ZSM‐5 zeolite which has atomically dispersed framework‐molybdenum homogenously distributed through the zeolite crystals. The introduction of Mo heals most of the native point defects in the zeolite structure resulting in an extremely stable material. The important features of this single‐site Mo‐containing ZSM‐5 zeolite are provided by an in‐depth spectroscopic and microscopic analysis. The material demonstrates superior thermal (up to 1000 °C), hydrothermal (steaming), and catalytic (converting methane to hydrogen and higher hydrocarbons) stability, maintaining the atomically disperse Mo, structural integrity of the zeolite, and preventing the formation of silanols. Abstract : A single‐site Mo‐containing nanosized ZSM‐5 zeolite with atomically dispersed framework‐molybdenum is synthesized. The zeolite displays superior stability, maintaining the atomically dispersed Mo, structural integrity of the zeolite, and preventing the formation of silanols.